Salinity stress-induced phosphorylation of INDETERMINATE-DOMAIN 4 (IDD4) by MPK6 regulates plant growth adaptation in Arabidopsis - Rawat, Anamika; Völz, Ronny; Sheikh, Arsheed; Mariappan, Kiruthiga G.; Kim, Soon-Kap; Rayapuram, Naganand; Alwutayd, Khairiah M.; Alidrissi, Louai K.; Benhamed, Moussa; Blilou, Ikram; Hirt, Heribert (Frontiers in Plant Science, 2023)
The INDETERMINATE DOMAIN (IDD) family belongs to a group of plant-specific transcription factors that coordinates plant growth/development and immunity. However, the function and mode of action of IDDs during abiotic stress, such as salt, are poorly understood. The genetic disruption of IDD4 increases salt-tolerance, characterized by sustained plant growth, improved Na + /K + ratio, and decreased stomatal density/ aperture. Yet, IDD4 overexpressing plants were hypersensitive to salt-stress with an increase in stomatal density and pore size. Transcriptomic and ChIP-seq analyses revealed that IDD4 directly controls an important set of genes involved in abiotic stress/salinity responses. Interestingly, using anti-IDD4-pS73 antibody we discovered that IDD4 is specifically phosphorylated at serine-73 by MPK6 in vivo under salinity stress. Analysis of plants expressing the phospho-dead and phospho-mimicking IDD4 versions proved that phosphorylation of IDD4 plays a crucial role in plant transcriptional reprogramming of salt-stress genes. Altogether, we show that salt stress adaption involves MPK6 phosphorylation of IDD4 thereby regulating IDD4 DNA-binding and expression of target genes.